Saifuddin, M PENGARUH KEBUTUHAN, TEMPAT, HARGA DAN PRODUK TERHADAP MINAT KULIAH KARYAWAN DI PAKUWON SUPERMALL (Nsc Press, 2015)
Preliminary data indicate a fact that the number of students who received at intervals over a period of 5 years Diploma program at NSC Surabaya Polytechnic has increased, while the capacity of classroom space is insufficient, hence the establishment of the second campus / college representative is needed, but before establishing a campus representatfif necessary research to prospective customers. The purpose of this study was to determine the influence of factors needs, place, price and product to interest college. From the results of the regression coefficients obtained showed variable NEEDS (X1 = 0.013) and variable PRODUCT (X3 = 0,040) had a significant positive effect, but significant levels of variable pricing and a> 0.05, so the result is not significantly so,and do not affect the interest of study in college